KEPATUHAN PRODUK GREEN FINANCING TERHADAP PRINSIP PRINSIP SYARIAH: ANALISIS FIQH MUAMALAH TERHADAP PEMBIAYAAN RAMAH LINGKUNGAN DI BANK SYARIAH - Rahmad, Rahmad (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2025)
This study aims to analyze the compliance of green financing products with Sharia principles based on the perspective of fiqh muamalah in Islamic banking. Green financing is a financial product designed to support environmentally friendly projects, which aligns with the growing global concern for sustainable development. This research uses qualitative methods, focusing on normative analysis of Sharia fiqh texts and contemporary banking practices. The findings indicate that green financing in Islamic banks upholds key principles of fiqh muamalah, particularly in promoting justice, prohibiting harm (la darar), and supporting social welfare through environmental sustainability.